Prevention of swelling of liver tumor in Sprague-Dawley rat fed with the Kinu-Mozuku, an edible Japanese brown alga grown at seashores in Noto-peninsula. - Hayakawa, Kou; Nagamine, Takeaki (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
Aim: Swelling of the tumor in the liver is difficult to stop by ordinary medicine. Then, newand safe drug preventing tumor-growth is required.Method: Three Sprague-Dawley rats, injected chemical carcinogen of diethyl- nitrosamine for12 weeks, are then fed the edible brown-alga Kinu-Mozuku, grown at seashores around Notopeninsula, Japan, for 3 weeks.Results: No liver tumor is found in three Kinu-Mozuku-fed sample rat. On the contrary, allthe three control-rats, fed without Mozuku, show very large tumor in their livers. Thisobservation is statistically significant (P = 0.05 by Mann-Whitney’s U test).   Conclusion: Japanese edible Kinu-Mozuku (Nemacystis decipiens) is proven to be the strongfoodstuff/drug preventing enlargement of liver-tumor in the outbred rat. Thus, the ediblefucoidan is expected to be the powerful and safe drug/medicine preventing and healing thehuman HCC and also the other intractable human cancers.